PENDAPAT POLITISI TERHADAP KREDIBILITAS LEMBAGA SURVEI TENTANG ELEKTABILITASNYA DALAM PEMILIHAN LEGISLATIF DPRD SULSEL 2014 - Andi Muhammad Abdi; Muhammad Iqbal Sultan; Hasrullah Hasrullah (KAREBA : Jurnal Ilmu Komunikasi, 2014)
Abstract The presence of survey’s institute hold a strategic role for a politicians as well as for the political party in every political moments, but the main requirement for a survey institute to maintain the public trust in them is their credibility. This study aims to find out politicians’ opinions and factors influencing their opinions about the credibility of survey institutions in relation with electability in the election of legislative representatives in South Sulawesi Parliament in 2014. This descriptive qualitative research involved twelve politicians from different parties and four survey institution officials as informants. They were selected purposively. The data were collected through interviews and observations; and were analysed by using the interaction analysis model developed by Milles and Huberman. The data were processed through three channels of qualitative data analysis: reducing the data, presenting the data, and drawing the conclusion. The results reveal that politicians tend to trust the credibility of survey institutions and the results of electability survey released by the institutions. This is influenced by internal and external factors. Internally, the politicians are influenced by their experience and education. Externally, they are influenced by party traditions and the credibility of survey institutions. Furthermore, according to the politicians. There are five criteria for credibility of a survey institutions, including track record of the institution, track record of the institution’s leader, proffesionality of human resources, positive image, and clear addres of office. Survey institutions maintain their relationship with politicians through emotional approach and professional approach. It is expected for the survey institutions to formulate a relevant method of survey for every existing political dynamis, such as for the money politics phenomena in the recent local elections. As for the politicians them selves, they have to be more selective and based on the ideal standard in utilizing the survey institutions.Abstrak Kehadiran lembaga survei memiliki peran strategis bagi seorang politisi maupun partai politik dalam setiap momentum politik, namun kredibilitas adalah syarat utama yang harus dimiliki suatu lembaga survei agar tetap dipercaya. Penelitian ini bertujuan untuk mengetahui pendapat politisi dan faktor-faktor apa yang mempengaruhi pendapat politisi terhadap kredibilitas lembaga survei mengenai elektabilitasnya dalam Pemilihan Legislatif DPRD Sulsel 2014. Penelitian ini bersifat deskriptif kualitatif. Informan penelitian ini adalah 12 orang politisi dari partai yang berbeda dan4 orang pimpinan lembaga survei. Pengambilan sampel dilakukan secara purposif. Pengumpulan data dilakukan melalui wawancara dan observasi. Data dianalisis dengan menggunakan analisis model interaksi yang dikembangkan oleh Milles dan Huberman, data yang telah didapat kemudian diolah melalui tiga jalur analisis data kualitatif yaitu: reduksi data, penyajian data dan penarikan kesimpulan. Penelitian ini menunjukkan bahwa politisi cenderung masih mempercayai kredibilitas lembaga survei dan hasil survei elektabilitasnya yang dirilis oleh lembaga survei. Faktor-faktor yang mempengaruhi pendapat politisi dilatar belakangi oleh faktor internal dan eksternal. Secara internal pendapat politisi dipengaruhi oleh faktor pengalaman dan pendidikannya sedangkan secara eksternal dipengaruhi oleh tradisi partai dan kredibilitas lembaga survei tersebut. Politisi mengungkapkan ada lima kriteria kredibilitas suatu lembaga survei yaitu: track record lembaga survei, track record pimpinan lembaga survei, sumber daya manusia profesional, citra positif dan memiliki kantor yang jelas. Strategi yang dilakukan oleh lembaga survei dalam menjaga hubungannya dengan politisi adalah melalui pendekatan yang bersifat emosional dan pendekatan yang bersifat profesional. Diharapkan lembaga survei dapat merumuskan metodologi survei yang relevan dalam setiap dinamika politik yang ada, seperti fenomena Money Politic yang terjadi di pileg. Kepada politisi diharapkan agar selektif dan berdasarkan standar yang ideal dalam menggunakan lembaga survei.